Preserving Malaysian cultural heritage from information management perspective / Siti Noorsiah Jamaludin, Razifah Othman and Mohd Nizam Yunus - Jamaludin, Siti Noorsiah; Othman, Razifah; Yunus, Mohd Nizam (Faculty of Information Management, 2015)
Cultural heritage is important to a civilization where it is often a legacy from generation to generation. Cultural Heritage is an expression of the ways of living developed by a community and passed through generations, including customs, practices, places, objects, artistic expressions and values. Through cultural heritage, a nation or society can create their own unique identity. Different countries have different cultural heritage although some neighbouring countries can have similarities in terms of intangible heritage but most do not. It is crucial to protect cultural heritage so that this unique identity can be preserved for the future. This article will discuss on how information management activities can have an impact in protecting cultural heritage.